2023
DOI: 10.1111/ajo.13692
|View full text |Cite
|
Sign up to set email alerts
|

Fathers attending the birth of their baby: Views, intentions and needs

Abstract: BackgroundThere is limited information about fathers' views, intentions and needs leading up to childbirth.AimsThis study explores the factors influencing fathers’ intention to attend the birth, and the needs and supports required leading up to childbirth.MethodsCross‐sectional survey of 203 prospective fathers attending antenatal appointments at an outer metropolitan public teaching hospital in Brisbane, Australia.ResultsA total of 201/203 (99.0%) participants intended to attend the birth. The reported reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…20 Most fathers felt well supported, although potential improvements include planning for future visits, providing information about childbirth, mental health support, better clinician communication, increased involvement in their partner's care, the opportunity to ask questions about childbirth and more frequent clinic visits. 20 Fathers who participate in antenatal classes benefit from a positive and satisfying experience. 21 However, a mixed-methods Australian study highlighted that 83% of expectant fathers report a lack of engagement with antenatal care due to time pressures, lack of knowledge, anxiety and barriers to attendance.…”
Section: The Forgotten Fathers In Obstetric Carementioning
confidence: 99%
See 3 more Smart Citations
“…20 Most fathers felt well supported, although potential improvements include planning for future visits, providing information about childbirth, mental health support, better clinician communication, increased involvement in their partner's care, the opportunity to ask questions about childbirth and more frequent clinic visits. 20 Fathers who participate in antenatal classes benefit from a positive and satisfying experience. 21 However, a mixed-methods Australian study highlighted that 83% of expectant fathers report a lack of engagement with antenatal care due to time pressures, lack of knowledge, anxiety and barriers to attendance.…”
Section: The Forgotten Fathers In Obstetric Carementioning
confidence: 99%
“…32,33 Several studies have identified that fathers wish to be included in perinatal healthcare and be engaged by health professionals about their health and well-being. 20,27,34,35 Although there is ample literature on paternal interventions that positively impact maternal-child outcomes, the postpartum role of the father is often ignored as an essential contributory factor in maternal decision-making. 1 Routine paternal screening and interventions can encourage positive perinatal care choices, health-seeking behaviours, and supportive maternal health decisions (eg reduced smoking and improved breastfeeding).…”
Section: The Forgotten Fathers In Obstetric Carementioning
confidence: 99%
See 2 more Smart Citations
“…The role of fathers in childbirth and infant care was explored by Kothari et al, who surveyed new fathers about their intentions, experiences, and needs around attending the birth of their children 11 . While most cultural norms now allow for and encourage active paternal engagement in birth, fathers identified several areas for potential improvement in health services to optimise their experience and contributions.…”
mentioning
confidence: 99%